2023
DOI: 10.3390/jcdd10030116
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Intravenous Iron Replacement Therapy on Cardiovascular Outcomes in Patients with Heart Failure: A Systematic Review and Meta-Analysis

Abstract: (1) Background: Iron deficiency (ID) is an important adverse prognostic marker in patients with heart failure (HF); however, it is unclear whether intravenous iron replacement reduces cardiovascular mortality in this patient group. Here, we estimate the effect of intravenous iron replacement therapy on hard clinical outcomes following the publication of IRONMAN, the largest trial in this field. (2) Methods: In this systematic review and meta-analysis, prospectively registered with PROSPERO and reported accordi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 36 publications
(115 reference statements)
0
4
0
Order By: Relevance
“…IV iron supplementation has bene cial effects in patients with heart failure, suggesting that iron acts directly on heart function (22). The possible mechanism may involve the important role of iron in cellular oxygen storage and cell metabolism in cardiomyocytes with a high energy demand (23).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…IV iron supplementation has bene cial effects in patients with heart failure, suggesting that iron acts directly on heart function (22). The possible mechanism may involve the important role of iron in cellular oxygen storage and cell metabolism in cardiomyocytes with a high energy demand (23).…”
Section: Discussionmentioning
confidence: 99%
“…RCTs have shown that IV iron improves exercise capacity and quality of life (24,25). In a meta-analysis of 12 RCTs of patients with heart failure, IV iron administration reduced hospitalization rate for heart failure, but the association with cardiovascular death was not signi cant (22). The PIVOTAL trial showed that high-dose IV iron resulted in a signi cantly lower risk of major nonfatal cardiovascular events compared with a lowdose regimen among HD patients (13).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, experimental models have demonstrated that the detrimental impact of iron deficiency on cardiac muscle can be reversed via iron supplementation [ 11 , 35 , 36 ]. In addition, clinical data have confirmed beneficial effects of iron supplementation in iron-deficient subjects in chronic conditions [ 37 , 38 ]. In patients with heart failure with left ventricular dysfunction, intravenous iron therapy leaded to improvement of symptoms, exercise capacity, and quality of life in randomized clinical trials, and was even associated with better prognosis in further meta-analysis [ 37 , 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, clinical data have confirmed beneficial effects of iron supplementation in iron-deficient subjects in chronic conditions [ 37 , 38 ]. In patients with heart failure with left ventricular dysfunction, intravenous iron therapy leaded to improvement of symptoms, exercise capacity, and quality of life in randomized clinical trials, and was even associated with better prognosis in further meta-analysis [ 37 , 38 ]. Recently, clinical data have shown favorable results of treatment of iron depletion in a post-acute clinical scenario: in patients who were stabilized after an episode of acute heart failure, a treatment with ferric carboxymaltose reduced the risk of heart failure hospitalizations in a randomized clinical trial [ 39 ].…”
Section: Discussionmentioning
confidence: 99%